PENERAPAN KONSEP KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN MATEMATIKA DI MADRASAH ALIYAH - Annisa, Nurul Hasanah; Khaidir, Christina; Susanto, Andi; Wahyuna, Fitra; Hasanah, Tiara Datul (UIN Imam Bonjol Padang, 2023)
Education always strives to create students who always make updates for the sake of updates all the time. Not only able to be highly educated but able to be an agent of change in small and large scopes. The resulting changes and innovations are able to provide maximum contribution to the progress of a nation that has quality human resources. This research aims to find out how the Independent Learning curriculum concept is implemented, especially in mathematics subjects at MAN 1 Padang. The method used is a qualitative research method using literature study. From the research conducted, MAN 1 Padang is a school that is still implementing the 2013 curriculum in the 2022/2023 academic year. Meanwhile, for the Merdeka Belajar curriculum, the Merdeka Belajar curriculum has already been introduced, but it is still in broad outline. Meanwhile, the implementation of the independent learning curriculum will only begin to be implemented in the new academic year 2023/2024.